Energetics of muscular exercise - Ferretti, G. (Springer, 2015)
This book discusses the maximal power and capacity of the three major biochemical pathways aerobic (oxygen consumption), anaerobic lactic (muscle lactate accumulation in absence of oxygen consumption), and anaerobic alactic (phosphocreatine hydrolysis) metabolism - as well as the factors that limit them. It also discusses the metabolic and cardio-pulmonary mechanisms of the dynamic response to exercise. The way and extent to which the power and capacity of the three major energy metabolisms are affected under a number of different conditions, such as training, hypoxia and microgravity, are also described. (Klappentext)